Chairside ceramic repair - Vimal Bharathi Bolloju; P Parameswar Naishadham; A Gautam Kumar; Sandhya Jadhav; M Praveen (Wolters Kluwer Medknow Publications, 2020)
Metal-ceramic restorations are used for fixed restorations very commonly, and sometimes, failure of these may need a removal and making a new restoration. It may destroy the abutment. Three categories of repair techniques are available for fractured metal-ceramic restorations, of which the treatment is chosen depending on the clinical acceptability. If the defects are small, these can be repaired intraorally with a ceramic repair kit without remaking the restoration. This article presents one such case report.